Introducing the liberal arts : a guidebook for English learners - Brown, Cherie; Reid, James; Sim, Malcolm; Williams, Clay (Emerald Publishing Limited, 2025)
Introducing the Liberal Arts: A Guidebook for English Learners offers students a broad introduction to the essential disciplines of a Liberal Arts education. Covering Humanities, Social Sciences, and Sciences, each of the 31 chapters--written by experienced professors--guides readers through subjects ranging from English Literature and Sociology to Biology and Physics. Each chapter provides context and explains the relevance of the subject to the overarching Liberal Arts curriculum, making this book an indispensable resource for those exploring or considering a Liberal Arts education. Building Academic Vocabulary for Success This book not only introduces readers to key academic subjects but also supports language learners by integrating high-frequency English words from the General Service List (GSL) and the Academic Word List (AWL). Each chapter highlights essential vocabulary in bold, helping learners focus on the most critical terms for both everyday and academic English. Accompanied by carefully curated vocabulary lists and glossaries, this approach ensures that students develop the language skills necessary for success in their academic journey. Engaging, Flexible Teaching Tool Designed for teachers and students alike, this book is a flexible resource that can be tailored to individual needs. Whether used as a supplemental text or a core part of the curriculum, the suggestions for group discussions, presentations, and writing exercises encourage active engagement with the material. By blending academic content with structured vocabulary development, this volume provides both an introduction to Liberal Arts disciplines and a pathway for improving English proficiency.